Method for preparing biomass hard carbon material through cooperation of ball milling oxidation and oxygen-enriched roasting, biomass hard carbon material and sodium ion battery
The preparation of biomass hard carbon materials through ball mill oxidation and oxygen-enriched roasting method has solved the problems of low sodium storage capacity and poor circulation performance of biomass hard carbon materials in the prior art, and achieved high sodium storage capacity and excellent circulation performance, and reduced the production costs.
Patent Information
- Application Number
- CN202411399948.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-09
Smart Images

Figure CN119461310A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery materials, and in particular relates to a method for preparing a biomass hard carbon material by ball milling oxidation and coordinated oxygen-enriched roasting, and the biomass hard carbon material and a sodium ion battery. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low cost, abundant sodium resources, and excellent safety performance, and are considered to be one of the most promising energy storage systems. Among them, carbon-based negative electrodes are recognized as the most commercially promising negative electrode materials, especially biomass-based hard carbon materials, which have the advantages of rich precursor sources and low prices and have attracted widespread attention. However, the current biomass-based hard carbon materials have problems such as low sodium storage capacity and poor cycle performance, and the current preparation methods of biomass-based hard carbon materials also have some technical problems: For example, the patent application with application number CN202210603915.6 discloses a biomass hard carbon based on low crystalline cellulose content and its preparation method and application, which pre-treats the biomass by acid hydrolysis, alkaline hydrolysis, etc., and then carbonizes and pyrolyzes it in an inert atmosphere to prepare biomass-derived hard carbon with high closed porosity. Because it uses chemical reagents, it is not environmentally friendly, and its process is complicated and the production cost is high. The patent application with application number CN202410068005.1 discloses a biomass hard carbon negative electrode material and its preparation method and application. It is prepared by pre-carbonizing agricultural waste in an inert atmosphere and then blending it with a modifier for modification. After impurities are removed, high-temperature carbonization is performed to obtain a hard carbon material. Since the modifier used is difficult to remove during impurity removal, it will affect the sodium storage performance of the hard carbon material. The patent application with application number CN202110907187.3 discloses a sodium ion battery carbon negative electrode material prepared based on waste sawdust and its preparation method. It uses waste sawdust as a precursor and is pre-carbonized in the air. However, the oxygen concentration is too low and the carbonization time is too short, making it difficult for the biomass to fully contact with oxygen, resulting in insufficient pre-oxidation, and a period of carbonization cannot accurately control the distribution of temperature and time during the carbonization process, thereby affecting the quality and performance of the final product. In addition, the energy consumption is high and it is not suitable for actual production. Summary of the invention
[0003] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, as well as a biomass hard carbon material and a sodium ion battery.
[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, comprising the following steps: (1) mixing biomass with an oxidizing agent and then subjecting the mixture to ball milling; the oxidizing agent is at least one of hydrogen peroxide, concentrated sulfuric acid, and persulfate; (2) placing the ball-milled oxidation product obtained after step (1) in an oxygen-rich atmosphere for calcination; wherein the oxygen concentration in the oxygen-rich atmosphere is not less than 30%; (3) subjecting the calcined product obtained after step (2) to low-temperature carbonization treatment under a protective atmosphere; (4) chemically removing impurities from the low-temperature carbonization product obtained after step (3); (5) The low-temperature carbonization product after chemical impurity removal in step (4) is subjected to high-temperature carbonization under a protective atmosphere to obtain a biomass hard carbon negative electrode material.
[0005] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (2), the oxygen-enriched atmosphere is a mixed atmosphere of oxygen and nitrogen, the roasting temperature is 150-350°C, and the holding time is 4-48h. The roasting temperature cannot be too low, otherwise the pre-oxidation is insufficient, the cross-linking is insufficient, and the material properties are affected; the roasting temperature cannot be too high, otherwise combustion will occur, affecting the yield.
[0006] By using an oxygen-rich atmosphere for roasting, organic macromolecules in biomass can be cross-linked to form more carbonyl functional groups, which is easy to form highly randomly oriented nanostructures in the subsequent carbonization process. In general, after oxygen-rich roasting, the degree of cross-linking of macromolecules in biomass is enhanced, the degree of graphitization in the carbonization process is suppressed, and a more disordered hard carbon material is obtained; the hard carbon material prepared by oxygen-rich roasting pretreatment has a higher carbonyl content, an increased interlayer spacing, and a greatly improved sodium storage capacity of the hard carbon material; after oxygen-rich roasting pretreatment, the O / C ratio of the material is reduced, the calorific value is improved, the yield of high-temperature carbonization is improved, the total yield is improved, and the production cost is reduced. The oxygen concentration in the oxygen-rich atmosphere is not less than 30%. If the oxygen concentration is low, the contact between oxygen and biomass is poor, the oxidation of biomass is insufficient, and the cross-linking is insufficient, which in turn affects the electrochemical performance. In order to further ensure sufficient oxidation during the oxygen-rich roasting process, the present invention achieves preliminary oxidation of biomass by adding an oxidizing agent during the ball milling process.
[0007] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (1), the rotation speed of the ball mill is 200-600 rpm, and the ball milling time is not less than 12 h.
[0008] During the ball milling process, the long-chain molecules in the biomass can be broken by physical action, and the weak chemical bonds (hydrogen bonds) can be cut by shear force, effectively reducing the degree of polymerization of the biomass organic molecules. The mechanical force can promote the generation of free radicals in the biomass molecules, and react with other molecules to form new chemical bonds. The heat and pressure generated during the ball milling process cause certain functional groups in the biomass to react and form new chemical bonds, which can achieve the initial cross-linking of the biomass components.
[0009] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (1), the ratio of the biomass to the oxidizing agent is 20:1 to 2:1.
[0010] The introduction of oxidizing agents during the ball milling process can promote the initial oxidation of biomass. The oxidizing agent takes hydrogen peroxide as an example to explain the initial oxidation process of biomass. Under alkaline conditions, hydrogen peroxide will dissociate to form peroxyhydroxyl ions, as shown in formula (1). The peroxyhydroxyl anions will act on the side chains of lignin to form hydroxylated products with a double bond structure of propylene structure and generate hydroxyl free radicals at the same time, as shown in formula (2). The hydroxylated intermediates will undergo a chain breaking reaction, resulting in a decrease in the degree of polymerization, as shown in formula (3).
[0011] H2O2+OH - ⇌ H2O+HOO - (1) R-CH=H-CH2-Ar+HOO - → R-CH(OH)-CH2-Ar+HO·(2) R-CH(OH)-CH2-Ar→ R-CHO+HO-CH2-Ar(3) Among them, R-CH=H-CH2-Ar represents the allyl structure on the side chain of lignin, Ar represents the aromatic ring structure of lignin, and R-CH(OH)-CH2-Ar is a hydroxylation intermediate.
[0012] Hydrogen peroxide will further dissociate with the peroxyhydroxyl anion to generate hydroxyl radicals and superoxide anion radicals, as shown in formula (4). Hydroxyl radicals can effectively oxidize the β-O-4 ether bonds between lignin and hemicellulose and the ester bonds of lignin, as shown in formulas (5) and (6), achieving initial pre-oxidation.
[0013] H2O2+HOO - → HO + O 2- +H2O (4) Ar-O-CH2-Ar1+HO·→ Ar-OH+Ar1-CHO (5) Ar-COO-R+HO· → Ar-COOH+RH (6) Among them, Ar-O-CH2-Ar1 represents two aromatics (Ar and Ar1) connected by a β-O-4 ether bond. The hydroxyl radical reacts with the ether bond, causing it to break, forming phenol (Ar-OH) and aldehyde (Ar1-CHO). Ar-COO-R represents the ester bond in lignin, Ar is the lignin aromatic ring, and R is the fatty acid chain. The hydroxyl radical reacts with the ester bond, causing it to break, forming carboxylic acid (Ar-COOH) and the corresponding alcohol or hydrocarbon (RH).
[0014] The residual hydrogen peroxide will decompose to produce oxygen and water during the roasting process, as shown in formula (7), which is beneficial to the pre-oxidation of biomass.
[0015] H2O2 → H2O+O2 (7) In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (2), the gas flow rate of the oxygen-enriched atmosphere is 0.1-4 L / h.
[0016] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (3), the temperature of low-temperature carbonization treatment is 400-800°C, and the holding time is 1-4 h. In the low-temperature carbonization process, the temperature is usually low, which is mainly used to remove volatiles in the precursor, and at the same time, the material is preliminarily carbonized to form a preliminary carbon structure. This stage helps to increase the charging amount and yield during the second stage of carbonization, and at the same time, the hard carbon structure is preliminarily formed, providing a stable foundation for subsequent carbonization. The present invention also performs high-temperature carbonization after low-temperature carbonization. The use of this two-stage carbonization method can more accurately control the temperature and time. Through crushing and particle size control, it helps to improve the specific surface area and median particle size of the hard carbon, thereby obtaining a higher quality hard carbon product, and can save energy consumption, reduce production costs, and meet the requirements of industrial production.
[0017] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation combined with oxygen-enriched roasting, preferably, the biomass is first soaked, washed, and dried, and then subjected to oxygen-enriched roasting.
[0018] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and coordinated oxygen-enriched roasting, preferably, the biomass is one of bamboo, reed, coconut shell, and fruit shell; the soaking time is 1-8h; the drying temperature is 50-100°C, and the drying time is 6-24h.
[0019] In the above-mentioned method for preparing biomass hard carbon materials by ball milling oxidation and coordinated oxygen-enriched roasting, preferably, in step (4), the chemical impurity removal includes alkaline leaching treatment and acid leaching treatment, and the reagent used in the alkaline leaching treatment is selected from one or several mixed solutions of sodium hydroxide, potassium hydroxide, and ammonia water, and the reagent used in the acid leaching treatment is selected from one or several mixed solutions of sulfuric acid, hydrochloric acid, nitric acid, and hydrofluoric acid.
[0020] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (5), the temperature of the high-temperature carbonization is 1000-1600°C, and the holding time is 1-4 h.
[0021] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, in step (3) and step (5), the protective atmosphere is at least one of nitrogen and argon, and the gas flow rate of the protective atmosphere is 0.1-4 L / h.
[0022] In the above-mentioned method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, preferably, the D50 of the biomass hard carbon material is 2-15 μm.
[0023] Based on a general inventive concept, the present invention also provides a biomass hard carbon material prepared by the above-mentioned preparation method.
[0024] Based on a general inventive concept, the present invention also provides a sodium ion battery, comprising the above-mentioned biomass hard carbon material.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses biomass, which is abundant in source and inexpensive, as raw material. By mixing it with an oxidizing agent and ball milling it, not only can the degree of polymerization of macromolecules in the biomass be reduced, exposing more free radicals, which is beneficial to the oxidation in the oxygen-enriched roasting process, but also the β-O-4 ether bonds between lignin and hemicellulose and the ester bonds of lignin can be preliminarily oxidized; the ball-milled and oxidized material is then subjected to oxygen-enriched roasting treatment, so that the organic molecules in the biomass are cross-linked, the degree of graphitization in the carbonization process is suppressed, and the prepared hard carbon material is more disordered and has excellent sodium storage performance.
[0026] (2) The oxygen-enriched roasting pretreatment adopted in the present invention can reduce the O / C ratio, improve the yield of the subsequent carbonization process, reduce energy consumption, increase the carbon yield, and effectively reduce the production cost.
[0027] (3) When the biomass hard carbon material of the present invention is used as a carbon-based negative electrode to prepare a sodium ion battery, it has the advantages of high sodium storage capacity and excellent cycle performance.
[0028] In general, the biomass hard carbon material of the present invention has a simple preparation process, low production cost, and high sodium storage capacity, which accelerates the industrialization process of biomass-based hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the XRD spectrum of the biomass-based hard carbon material prepared in Example 1 of the present invention.
[0030] Figure 2 This is a TEM image of the biomass-based hard carbon material prepared in Example 1 of the present invention.
[0031] Figure 3 This is the first cycle charge and discharge curve of the biomass-based hard carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0035] The following is the carbon yield of the hard carbon material involved in the examples and comparative examples = (mass of the prepared hard carbon material / mass of the original biomass) * 100%.
[0036] Embodiment 1: A method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting of the present invention comprises the following steps: (1) Raw material processing: Soak the bamboo in distilled water for 2 h, wash it, dry it at 80 °C for 18 h, and pre-crush it; (2) Ball milling oxidation: The pre-crushed bamboo was mixed with a hydrogen peroxide solution with a pH of 11 and a concentration of 0.3 g / mL at a solid-liquid ratio of 1:1 g / mL and ball milled at a speed of 400 rpm for 24 h. (3) Oxygen-enriched calcination: The ball-milled oxidized bamboo was added into a heating furnace and calcined at 250°C at a heating rate of 5°C / min for 24 h in an oxygen-enriched atmosphere. The oxygen-enriched atmosphere was a mixture of 50% oxygen and 50% argon at a flow rate of 0.3 L / h. After the calcination, the mixture was cooled to room temperature to obtain an oxygen-enriched calcined product. (4) Low-temperature carbonization: The oxygen-enriched calcined product was heated to 500 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonized product was obtained. (5) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1 mol / L and hydrofluoric acid having a concentration of 3 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product; (6) High-temperature carbonization: The impurity-removed product obtained in step (5) is subjected to high-temperature carbonization at a heating rate of 5°C / min to 1500°C under the protection of argon gas. The carbonization holding time is 2 h, and the argon gas flow rate is 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product is obtained. (7) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain D 50 =10 μm, that is, biomass-based hard carbon material.
[0037] The carbon yield of the hard carbon material prepared in this example is 29.33%.
[0038] The XRD spectrum of the biomass-based hard carbon material prepared in this example is as follows: Figure 1 As shown, it can be seen from the XRD spectrum that two severely broadened diffraction peaks appear near 23° and 43°, which correspond to the diffraction crystal planes of (002) and (101), respectively, indicating that the material prepared in this example is an amorphous carbon material.
[0039] The TEM image of the biomass-based hard carbon material prepared by the present invention is as follows: Figure 2 As shown in the figure, it can be seen that the biomass-based hard carbon material prepared in this embodiment has a high degree of disorder and a relatively large number of closed-pore structures.
[0040] The hard carbon material prepared in this example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and its electrochemical performance was measured: The hard carbon material powder prepared in this embodiment is mixed with acetylene black and PVDF in a mass ratio of 90:5:5, and then a proper amount of organic solvent NMP is added to grind to form a slurry, and then the grinded slurry is evenly coated on the current collector copper foil, and after drying, it is cut into circular pole pieces. The pole pieces are dried at 120°C for 6 hours under vacuum conditions and then transferred to a glove box for use.
[0041] The simulated battery was assembled in a glove box with an Ar atmosphere, using metallic sodium as the counter electrode and 1 mol of NaPF6 dissolved in 1 L of a 1:1 volume ratio of ethylene carbonate and diethyl carbonate solution as the electrolyte to form a CR2032 button cell. The constant current charge and discharge mode was used to perform charge and discharge tests at a current density of 0.1C. Figure 3 As shown, under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity is 325.41 mAh / g, the coulombic efficiency in the first week is 87.13%, and the capacity retention rate is as high as 95.80% after 100 cycles at a current density of 1.0 C.
[0042] Embodiment 2: A method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting of the present invention comprises the following steps: (1) Raw material processing: Soak the coconut shell in distilled water for 2 h, wash it, dry it at 90 °C for 12 h, and pre-crush it; (2) Ball milling oxidation: The pre-crushed coconut shell was mixed with a hydrogen peroxide solution with a pH of 10 and a concentration of 0.2 g / mL at a solid-liquid ratio of 1:1 g / mL and ball milled at a speed of 400 rpm for 16 h. (3) Oxygen-enriched roasting: add the ball-milled oxidized coconut shell into a heating furnace and roast it at 180°C at a heating rate of 5°C / min for 18 h in an oxygen-enriched atmosphere. The oxygen-enriched atmosphere is a mixture of 50% oxygen and 50% argon, and the flow rate of the mixed gas is 0.3 L / h. After the roasting, cool it to room temperature to obtain an oxygen-enriched roasted product. (4) Low-temperature carbonization: The oxygen-enriched calcined product was heated to 500 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonized product was obtained. (5) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 4 mol / L for 6 h; and then subjected to acid leaching treatment with a hydrochloric acid solution having a concentration of 2 mol / L for 6 h to remove impurity elements and obtain an impurity-removed product; (6) High-temperature carbonization: The impurity-removed product was heated to 1400°C at a heating rate of 5°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 3 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained. (7) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain D 50 =12 μm, that is, biomass-based hard carbon material.
[0043] The carbon yield of the hard carbon material prepared in this example is 28.83%.
[0044] The biomass-based hard carbon material of this embodiment is used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test is carried out, and the preparation process and test method are the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity is 319.23 mAh / g, the first week coulomb efficiency is 86.90%, and the capacity retention rate after 100 cycles at a current density of 1.0 C is 95.17%.
[0045] Embodiment 3: A method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting of the present invention comprises the following steps: (1) Raw material processing: Soak the bamboo in distilled water for 4 h, wash it, dry it at 90 °C for 12 h, and pre-crush it; (2) Ball milling oxidation: The pre-crushed bamboo was mixed with a hydrogen peroxide solution with a pH of 11 and a concentration of 0.4 g / mL at a solid-liquid ratio of 1:1 g / mL and ball milled at a speed of 300 rpm for 24 h. (3) Oxygen-enriched calcination: The ball-milled oxidized bamboo was added into a heating furnace and calcined at 200 °C at a heating rate of 5 °C / min for 24 h in an oxygen-enriched atmosphere. The oxygen-enriched atmosphere was a mixture of 80% oxygen and 20% argon, and the flow rate of the mixture was 0.3 L / h. After the calcination, the mixture was cooled to room temperature to obtain an oxygen-enriched calcined product. (4) Low-temperature carbonization: The oxygen-enriched calcined product was heated to 600 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonized product was obtained. (5) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1 mol / L and hydrofluoric acid having a concentration of 3 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product; (6) High-temperature carbonization: The impurity-removed product was heated to 1500°C under the protection of argon at a heating rate of 5°C / min for high-temperature carbonization. The carbonization holding time was 3 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained. (7) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain D 50 =12 μm, that is, biomass-based hard carbon material.
[0046] The carbon yield of the hard carbon material prepared in this example is 28.26%.
[0047] The biomass-based hard carbon material prepared in this embodiment is used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test is carried out, and the preparation process and the test method are the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity is 320.87 mAh / g, the first-week coulomb efficiency is 86.30%, and the capacity retention rate after 100 cycles at a current density of 1.0 C is 94.88%.
[0048] Comparative Example 1: The difference between this comparative example and Example 1 is that there is no oxygen-enriched roasting pretreatment, and the remaining steps are the same as those in Example 1. The specific steps are as follows: (1) Raw material processing: Soak the bamboo in distilled water for 2 h, wash it, dry it at 80 °C for 18 h, and pre-crush it; (2) Ball milling oxidation: The pre-crushed bamboo was mixed with a hydrogen peroxide solution with a pH of 11 and a concentration of 0.3 g / mL at a solid-liquid ratio of 1:1 g / mL and ball milled at a speed of 400 rpm for 24 h. (3) Low-temperature carbonization: The material ball-milled and oxidized in step (2) was subjected to low-temperature carbonization at a heating rate of 5°C / min to 500°C under the protection of argon gas. The carbonization holding time was 2 h, and the flow rate of argon gas was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained. (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1 mol / L and hydrofluoric acid having a concentration of 3 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product; (5) High-temperature carbonization: The impurity-removed product was heated to 1500°C under the protection of argon at a heating rate of 5°C / min for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained. (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain D 50 =10 μm, that is, biomass-based hard carbon material.
[0049] The carbon yield of the hard carbon material prepared in this comparative example is 24.43%.
[0050] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 291.09 mAh / g, the first-week coulomb efficiency was 82.66%, and the capacity retention rate after 100 cycles at a current density of 1.0 C was only 82.90%.
[0051] Comparative Example 2: The difference between this comparative example and Example 1 is that there is no oxidation ball milling treatment, and the other steps are the same as Example 1.
[0052] (1) Raw material processing: Soak the bamboo in distilled water for 2 h, wash it, dry it at 80 °C for 18 h, and pre-crush it; (2) Oxygen-enriched roasting: The pre-crushed bamboo is added into a heating furnace and roasted at 250°C at a heating rate of 5°C / min for 24 h in an oxygen-enriched atmosphere. The oxygen-enriched atmosphere is a mixture of 50% oxygen and 50% argon, and the flow rate of the mixed gas is 0.3 L / h. After the roasting, the mixture is cooled to room temperature to obtain an oxygen-enriched roasted product. (3) Low-temperature carbonization: The oxygen-enriched calcined product was heated to 500 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonized product was obtained. (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1 mol / L and hydrofluoric acid having a concentration of 3 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product; (5) High-temperature carbonization: The impurity-removed product obtained in step (4) is subjected to high-temperature carbonization at a temperature of 1500°C at a heating rate of 5°C / min under the protection of argon gas. The carbonization holding time is 2 h, and the argon gas flow rate is 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product is obtained. (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain D 50 =10 μm, that is, biomass-based hard carbon material.
[0053] The carbon yield of the hard carbon material prepared in this comparative example is 28.78%.
[0054] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 310.30 Ah / g, the first-week coulomb efficiency was 85.92%, and the capacity retention rate after 100 cycles at a current density of 1.0 C was 91.09%.
[0055] Comparative Example 3: The difference between this comparative example and Example 1 is that the oxygen-enriched roasting pretreatment is changed to air roasting, and the remaining steps are the same as those in Example 1. The specific steps are as follows: (1) Raw material processing: Soak the bamboo in distilled water for 2 h, wash it, dry it at 80 °C for 18 h, and pre-crush it; (2) Ball milling oxidation: The pre-crushed bamboo was mixed with a hydrogen peroxide solution with a pH of 11 and a concentration of 0.3 g / mL at a solid-liquid ratio of 1:1 g / mL and ball milled at a speed of 400 rpm for 24 h. (3) Air calcination: The ball-milled and oxidized bamboo was added into a heating furnace and calcined at 250°C at a heating rate of 5°C / min for 24 h in an air atmosphere. The flow rate of the mixed gas was 0.3 L / h. After the calcination, the bamboo was cooled to room temperature to obtain a calcined product. (4) Low-temperature carbonization: The calcined product was heated to 500 °C at a heating rate of 5 °C / min under the protection of argon gas for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonized product was obtained. (5) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1 mol / L and hydrofluoric acid having a concentration of 3 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product; (6) High-temperature carbonization: The impurity-removed product was subjected to high-temperature carbonization at a heating rate of 5°C / min under the protection of argon gas. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained. (7) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain D 50 =10 μm, that is, biomass-based hard carbon material.
[0056] The carbon yield of the hard carbon material prepared in this comparative example is 26.89%.
[0057] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 309.45 Ah / g, the first-week coulomb efficiency was 84.71%, and the capacity retention rate after 100 cycles at a current density of 1.0 C was 90.31%.
[0058] Comparative Example 4: The difference between this comparative example and Example 1 is that the carbonization process is a one-stage carbonization, and the remaining steps are the same as those in Example 1. The specific steps are as follows: (1) Raw material processing: Soak the bamboo in distilled water for 2 h, wash it, dry it at 80 °C for 18 h, and pre-crush it; (2) Ball milling oxidation: The pre-crushed bamboo was mixed with a hydrogen peroxide solution with a pH of 11 and a concentration of 0.3 g / mL at a solid-liquid ratio of 1:1 g / mL and ball milled at a speed of 400 rpm for 24 h. (3) Oxygen-enriched calcination: The ball-milled oxidized bamboo was added into a heating furnace and calcined at 250°C at a heating rate of 5°C / min for 24 h in an oxygen-enriched atmosphere. The oxygen-enriched atmosphere was a mixture of 50% oxygen and 50% argon at a flow rate of 0.3 L / h. After the calcination, the mixture was cooled to room temperature to obtain an oxygen-enriched calcined product. (4) High-temperature carbonization: The oxygen-enriched calcined product was heated to 1500°C under the protection of argon at a heating rate of 5°C / min for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained. (5) Impurity removal treatment: The high-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1 mol / L and hydrofluoric acid having a concentration of 3 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product; (6) Crushing and classification: The impurities are crushed by air flow to obtain D 50 =10 μm, that is, biomass-based hard carbon material.
[0059] The carbon yield of the hard carbon material prepared in this comparative example is 29.50%.
[0060] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 315.03 Ah / g, the first-week coulomb efficiency was 85.35%, and the capacity retention rate after 100 cycles at a current density of 1.0 C was 93.99%.
Claims
1. A method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting, characterized in that: The following steps are involved: (1) mixing biomass with an oxidizing agent and then subjecting the mixture to ball milling; the oxidizing agent is at least one of hydrogen peroxide, concentrated sulfuric acid, and persulfate; (2) placing the ball-milled oxidation product obtained after step (1) in an oxygen-rich atmosphere for calcination; wherein the oxygen concentration in the oxygen-rich atmosphere is not less than 30%; (3) subjecting the calcined product obtained after step (2) to low-temperature carbonization treatment under a protective atmosphere; (4) chemically removing impurities from the low-temperature carbonization product obtained after step (3); (5) The low-temperature carbonization product after chemical impurity removal in step (4) is subjected to high-temperature carbonization under a protective atmosphere to obtain a biomass hard carbon negative electrode material.
2. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting as claimed in claim 1, characterized in that: In step (1), the mass ratio of the biomass to the oxidizing agent is 20:1-2:1; the rotation speed of the ball mill is 200-600 rpm, and the ball milling time is not less than 12 h.
3. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting as claimed in claim 1, characterized in that: In step (2), the oxygen-rich atmosphere is a mixed atmosphere of oxygen and nitrogen, the calcination temperature is 150-350° C., and the holding time is 4-48 h; the gas flow rate of the oxygen-rich atmosphere is 0.1-4 L / h.
4. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting as claimed in claim 1, characterized in that: In step (3), the temperature of the low-temperature carbonization treatment is 400-800°C, and the insulation time is 1-4 h.
5. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting as claimed in claim 1, characterized in that: The biomass is at least one of bamboo, reed, coconut shell and fruit shell.
6. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting as claimed in claim 1, characterized in that: In step (4), the chemical impurity removal includes alkaline leaching and acid leaching. The reagent used in the alkaline leaching is selected from one or a mixed solution of sodium hydroxide, potassium hydroxide, and ammonia water. The reagent used in the acid leaching is selected from one or a mixed solution of sulfuric acid, hydrochloric acid, nitric acid, and hydrofluoric acid.
7. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting as claimed in claim 1, characterized in that: In step (5), the high temperature carbonization temperature is 1000-1600°C, and the insulation time is 1-4 h.
8. The method for preparing biomass hard carbon material by ball milling oxidation and oxygen-enriched roasting according to claim 1, characterized in that: In step (3) and step (5), the protective atmosphere is at least one of nitrogen and argon, and the gas flow rate of the protective atmosphere is 0.1-4 L / h.
9. A biomass hard carbon material, characterized in that: The method according to any one of claims 1 to 8 is used to prepare the present invention.
10. A sodium ion battery, characterized in that: Including the biomass hard carbon material as described in claim 9.
Citation Information
Patent Citations
Sodium-ion battery carbon negative electrode material prepared based on waste wood chips and preparation method thereof
CN113651307A
A biomass hard carbon based on low crystalline cellulose content and its preparation method and application
CN115064667B
Biomass hard carbon negative electrode material and preparation method and application thereof
CN117945387A
Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material
CN113381016A
Sodium ion battery and biomass hard carbon negative electrode material and preparation method thereof
CN116675217A
Cited By
Phosphorus-doped biomass-based hard carbon material, negative electrode, sodium ion battery and preparation method
CN121063515A